PENGARUH PENGGUNA MEDIA ONLINE TERHADAP PERILAKU CYBERBULLYING PADA TAYANGAN YOUTUBE YUSI FADILLA - Rafiqoh, Rafiqoh; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2020)
This study is aimed to determine the impact of online media users of a cyberbullying behavior on yusi fadila's youtube channel. This research used the quantitative method with Spiral of Silence theory to examine from the media mass side and General Aggression Model (GAM) theory to examine from cyberbullying perpetrators side. The sampling technique using the simple random sampling. The result of this study show that the users of online media can affect the result of cyberbullying behavior on youtube especially on yusi fadila's youtube channel. The variables obtained 52,4% and correlate with each other. Keyword:Youtube , cyberbullying, online media user